Business Development Strategy at PT Sentosa Jaya Teknik Bandar Lampung Using the Business Model Canvas (BMC) Approach - Cindy Aprilia; M. Oktaviannur (Rescollacom (Research Collaborations Community), 2026)
This study aims to develop an appropriate business strategy for PT Sentosa Jaya Teknik based on the Business Model Canvas. This type of research uses descriptive research with a qualitative approach. The informants in this study are the owner, employees, and consumers of PT Sentosa Jaya Teknik. The data collection techniques used are semi-structured interviews and documentation. The results of this study from the identification of the Business Model Canvas provide appropriate strategic development options for PT Sentosa Jaya Teknik in each element. The customer segment element shows that the company focuses on all expedition services. The value proposition element adds innovation. The channel element uses manual channels. The customer relationship element shows that the company provides newsletters. The revenue streams element adds new streams. The key resources element focuses on employee education for innovation. The key activities element focuses on product development. The key partnerships element shows the large number of partners of PT Sentosa Jaya Teknik. Meanwhile, the last element, namely the cost structure of PT Sentosa Jaya Teknik, consists of fixed costs and variable costs. The appropriate strategy for PT Sentosa Jaya Teknik is the weakness opportunities (WO) strategy.